Lingvosemiotic Aspect of Fairy Tales - Syzdykova, Г.О.; Sholakova, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
Analyzing the folk magic tales of the world, we can be sure that fairy tales were created using a common structural model. The model of similarity in such a content network was compiled by the Russian linguist V.Ya.Propp. This revolution in the study of folk tales occurred after the publication of the book by V. Ya. Propp “The Morphology of a Fairy Tale”, which opened the way for new research in the framework of structuralsemiotic linguistics. “All researchers agree that the beginning of the structural study of narrative texts was laid by the“ Morphology of a Fairy Tale ”by V. Ya. Propp, published in 1928” The article discusses the linguosemiotic aspect of fairy tales. The object of the study is the Kazakh fairy tale - “Yer Toast”. Made lingvo-semiotic analysis of a fairy tale